PON XXI Survey in North Sumatra on High School Students - Timbul Mugabe Siregar; Samsuddin Siregar; Amir Supriadi; Rafika Ardilla (UNIB Press, 2023)
This study aims to measure the knowledge of high school students about PON XXI which will be held in North Sumatra - Aceh in 2024. This research uses a qualitative descriptive method with survey techniques. The sample for this research was 192 people from several schools with 3 districts/cities namely area of ​​Medan city, Deli Serdang Regency, and Serdang Bedagai Regency. Data collection techniques using observation and questionnaires. Based on research results from the questionnaire, information was obtained that 47 students (23.9%) had never heard of PON 93 people (47.2%) students did not understand about PON 37 people (17.3%) students did not know at all how many years PON was held. 16 people (8.1%) students did not know where the host of PON XXI would be held; and 118 people (59.9%) students responded to know the attributes of PON XX in Papua. From the results of the data obtained, it is known that there are still many high school/equivalent students who do not know about the grand PON event which will be held in 2024 in North Sumatra and Aceh. It can be seen from the average percentage obtained by 31.3% of students who do not have knowledge about PON and the events that will be held in 2024.It can be concluded that it is necessary to carry out socialization about PON XXI which will be held in North Sumatra - Aceh in 2024.